The influence of carbon nanotube buckypaper/poly (ether imide) mats on the thermal properties of poly (ether imide) and poly (aryl ether ketone)/carbon fiber laminates - Santos, Luis Felipe de Paula [UNESP]; Alderliesten, René; Kok, Winand; Ribeiro, Bruno; de Oliveira, Juliana Bovi [UNESP]; Costa, Michelle Leali [UNESP]; Botelho, Edson Cocchieri [UNESP] (Elsevier, 2021)
The use of carbon nanotube buckypapers (BP) has boosted their use in polymeric composites. However, their low permeability makes processing difficult and limits their use. This work's essential contribution is to define the best parameters to process the buckypapers through vacuum filtration technique and the use of electrospun poly (ether imide) (PEI) mats as a substrate during the BP processing to favor matrix/nanoparticle adhesion and improving the handling. Three different sonication power (50, 75, and 100 W) were used in the buckypaper processing to evaluate its influence. From the results obtained, the chosen power was 100 W due to large pore dimensions (100-200 nm) and a more significant structural order observed through L002 (crystallite size) of 2.80. The addition of BP/PEI mats favored an increase in PEI laminates' thermal stability by increasing its initial decomposition temperature by 10 °C and an increase of 9 °C in the glass transition temperature. For poly (aryl ether ketone) (PAEK) laminates, the addition of BP/PEI mats did not impact thermal stability and melting temperature but promoted a 6 °C reduction in crystallization temperature. On the other hand, the BP without PEI mats promoted a reduction of the studied properties, which can be associated with a lousy impregnation of the matrix in the buckypaper resulting in a weak interface. DMA analyses show that BP/PEI in both laminates (PEI and PAEK) favored the interaction between the constituents and present a larger region of interphase compared to BP without PEI/mats thus optimizing the load transfer throughout the interface.
Keywords: Buckypapers; Electrospinning; Thermal analysis; Viscoelastic properties